Menggelorakan makna energik sebagai brandscape erigo melalui iklan fireflies - Kurniawan, Febryan; Isnaini, Muhammad; Marta, Rustono Farady (Jurnal Komunikasi Profesional, 2021)
Local brands in Indonesia today are growing and competitive and in this competition, various appropriate marketing communication strategies are needed, where this is needed to build attention from potential consumers. One of the local brands from Indonesia is Erigo, a company that has recently been discussed by internet users because one of its marketing strategies is to place advertisements in Time Square, New York. Advertising is one of the digital marketing strategies that serves to attract the attention of potential consumers through information on products and services offered to stick in the minds of consumers. Through a qualitative approach with an interpretive paradigm using Laura R. Oswald's marketing semiotics method, it was found that through the short advertisement "Fireflies", Erigo wanted to show the target audience and their target market, young people or millennials, to have enthusiasm, motivation and belief. high self-esteem in exploring their curiosity, one of which can be done by real action from their energetic nature. This energetic nature becomes an ideology (cultural categories) that Erigo wants to convey to its target market, which are young people who aim to convey an invitation to dare to explore new things to find hope and identity related to exploratory (cultural tensions). Exploratory is meant here is a sense of freedom (emotional territories) where this is necessary for them to inflame the energetic they have.